Disorder phenomena in Nd-doped (Pr1-xNdx)0.67Ba0.33MnO3 manganites - H. Abdullah,; S.A. Halim, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Polycrystalline samples of (Pr1-xNdx)0.67Ba0.33MnO3 with x = 0.0, 0.167, 0.33, 0.5, 0.67, 0.833, and 1.0 have been prepared using the solid state reaction. The samples were calcined at 900oC for 12 hours, pelletized and sintered at 1300oC for 24 hours. The structures were investigated via X-ray diffraction (XRD) method. XRD patterns showed orthorhombic distorted perovskite structures. The scanning electron microscopy (SEM) micrographs showed the disorder of the structure in all substitutions. This influenced the value of the magnetoresistance (MR). The MR effects are measured using the four point probe technique with a magnetic field of B ≤ 1T at temperatures of 90, 100, 150, 200, 250, 270 and 300 K. Overall, the MR increased as the temperature decreased. All doping concentrations gave a small variation range (~10% to ~56%). The highest MR value of 56.5 % is observed at 100 K for a sample with x = 1.0. The influence of disorder on the magnetoresistance in (Pr1-xNdx)0.67Ba0.33MnO3 manganites at low temperatures was also discussed in this paper.